Influence Of Teacher Characteristics On Students' Academic Achievement Among Senior High Schools In Ogan Komering Ulu - Sanda, Silfi (English Education Department, Universitas Islam Indonesia, 2013)
In UU No. 14/2005 state that all teacher should have pedagogy, social, professional and personality competencies. One of the important competencies is personality competence. According to Moorhead & Griffin (2010), there are five traits which is related to the organizational behavior called “big five personality traits”. Those are agreeableness, conscientiousness, negative emotionality, extraversion and openness. The purpose of this study was to establish the relationship between teacher characteristics and students' academic achievement. The study was guided by Education Production Function theory (EPF) which connects student academic achievement to teacher characteristics. The study was conducted in Ogan Komering Ulu, the target population comprised of teachers of all 20 senior high schools. The study applied a causal comparative research design. A questionnaire was used for data collection. Data was analyzed using descriptive and inferential statistical techniques. The study findings suggest that there was no significant relationship between teacher qualification and student academic achievement.Keywords: Teacher characteristics, academic achievement, experience and Qualification